Policy Analysis of Land Tenure Settlement in the Context of Forest Area Management in Kampung Bukit Makmur, Segah District and Management in Labanan Makarti Village, East Kalimantan Province - Yanto; Rosmini; Jawatir Pardosi; Ndan Imang; Marlon Ivanhoe Aipassa; Yunianto Setiawan (JURNAL AGRIMENT, 2025)
Land tenure issues in forest areas are strategic issues in the context of sustainable development, agrarian reform, and social justice-based natural resource management. This study analyses the land tenure settlement policy in the context of forest area management in Kampung Bukit Makmur and management in Kampung Labanan Makarti, Berau Regency, East Kalimantan. The method of this research using qualitative approach with document study techniques, in-depth interviews, and participatory observation. The analysis was conducted using a public policy framework, tenure approach, and principles of good governance. The results show that the implementation of the Land Tenure Settlement in Forest Areas (PPTKH) policy was arranged by Presidential Regulation No. 88/2017 there are challenge remains at the local level, including: unsuitability between forest area mapping and the reality of land use by public, the weakness coordination between government agencies, limited accurate spatial data, and less of community participation on the inventory and verification process. Nevertheless, there are strategic opportunities to encourage fair and sustainable settlements through the utilization of forest area release schemes, social forestry, and integration with agrarian reform policies. This recommendation of this study need reinforcement from local institutions, acceleration of participatory mapping, increasing community capacity, and need to create formula of technical policies that are responsive to local social-ecological conditions. Settlement of land tenure in forest areas does not only concern on legal-formal aspects, but also include on the dimensions of social justice, acknowledgment of the rights of indigenous/local communities, and preservation of the ecological functions of forest areas.